Swedish guidelines for device‐aided therapies in Parkinson's disease —Economic evaluation and implementation. (26th April 2021) - Norlin, Jenny M.; Willis, Michael; Persson, Ulf; Andersson, Emelie; E. Pålhagen, Sven; Odin, Per
Abstract : Objectives: The National Board of Health and Welfare in Sweden published the national guidelines for Parkinson's Disease 2016. The aim of this study was to summarize this evidence review and development of the guidelines, focusing on the economic evaluation of device‐aided therapies (deep brain stimulation, pump‐based infusion of levodopa‐carbidopa intestinal gel or apomorphine) for Parkinson's disease, and the rate of implementation after 3 years in Sweden. Material and methods: The evidence review underlying the guidelines—including systematic literature searches of clinical and economic evidence, model‐based economic evaluation, and formal analysis and guideline development—was examined, condensed, and translated. The impact of the guidelines was assessed with treatment use statistics from 2009 to 2019. Results: All device‐aided therapies were assigned high priority. Based on a relatively low proportion of device‐aided therapies (30%) in Parkinson's disease, a 5‐year increase of 500 patients was recommended. This was estimated to reduce total costs by SEK 14 million (€1.7 million). Follow‐up data found an increase of 217 patients between 2017 and 2019, following the same trend as before the guidelines. Conclusion: Three years after the guidelines were published, the use of device‐aided therapies has increased in Sweden, albeit not in pace with recommendations. One reason for slow implementation may be poor incentivization related to budget silos in which the costs for device‐aided therapies are borne by the regions but the cost offsets (eg, reduced need for home care) are reaped by local stakeholders.